2020
DOI: 10.28959/jdpi.v31i1.5878
|View full text |Cite
|
Sign up to set email alerts
|

Efek Modifikasi Plasma Untuk Meningkatkan Sifat Tahan Api Dari Kain Katunfect of Plasma Modification for Improving Fire Retardant Properties of Cotton Fabric

Abstract: Pada penelitian ini telah dikembangkan sifat tahan api pada bahan tekstil kain katun dengan menggunakan resin tahan api dan ekstrak daun bayam. Zat tahan api diaplikasikan pada kain katun dengan menggunakan metode plasma bertekanan atmosfir dan pad-dry-cure. Kain katun yang digunakan merupakan kain kapas yang telah mengalami proses pengelantangan dan merserisasi. Pada penelitian ini telah dilakukan tiga jenis metode, yaitu metode pad-dry-cure pada zat resin tahan api dengan pra-perlakuan plasma bertekanan atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
0
5
0
5
Order By: Relevance
“…The use of electronic devices has been increased rapidly in recent years. Several researchers (Al-Saleh & Sundararaj, 2009;Avloni et al, 2007;Ma et al, 2014;Mariotti et al, 2016;Morent et al, 2008;Putra, Mohamad, & Wijayono, 2020) have shown the application of the use of physics in the case of textiles both in materials science and environmental engineering especially in smart and functional material. The application of physics and chemistry, especially in some textile industries, has been widely applied (e.g., plasma physics in textile processes, the electromagnetic field for EMI Shielding, etc.).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of electronic devices has been increased rapidly in recent years. Several researchers (Al-Saleh & Sundararaj, 2009;Avloni et al, 2007;Ma et al, 2014;Mariotti et al, 2016;Morent et al, 2008;Putra, Mohamad, & Wijayono, 2020) have shown the application of the use of physics in the case of textiles both in materials science and environmental engineering especially in smart and functional material. The application of physics and chemistry, especially in some textile industries, has been widely applied (e.g., plasma physics in textile processes, the electromagnetic field for EMI Shielding, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Chen, Lee, Lin, & Koch, 2007;Cheng et al, 2015;Hwang, Chen, Lou, & Lin, 2014;Kumar et al, 2015;Li, Zhang, & Yin, 2012;Ozen, Usta, Yuksek, Sancak, & Soin, 2018) in the field of textiles are currently trying to make anti-radiation clothing with a material and coating process that is simple and affordable but also has good washing test resistance. Some researchers (Boonchoat, Satreerat, & Hodak, 2010;Jung & Choi, 2007;Lieberman & Lichtenberg, 1994;Murti & Putra, 2020;Putra, Fitri, Purnama, & Mohamad, 2020;Putra, Mohamad, & Wijayono, 2020;Putra, Mohamad, & Yusuf, 2020) stated that the method of radiation exposure by plasma generators has been shown to strengthen the adhesive material coating force and is proven effective in absorbing the material to be deposited. Some researchers (Ozen et al, 2018;Putra, Fitri, et al, 2020) also stated that to obtain anti-radiation material, the textile fabric must have a conductive property but not oxidize easily, one example of the recommended material is carbon black.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations